Pengaruh Motivasi Belajar Terhadap Konsentrasi Belajar Siswa SDIT Wahdah Islamiyah 01 Makassar - Fatimah, Shakila Dewi; Alwi, M. Ahkam (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Learning is the main activity in the education process and is a benchmark for the success or failure of the education process and goals. Success in the learning process to achieve learning goals is influenced by good concentration. However, not a few students who pay less attention to lessons are caused by lack of concentration which is closely related to motivation in learning. This study aims to see the effect of learning motivation on the learning concentration of students at SDIT Wahdah Islamiyah 01 Makassar. The sampling technique used the cluster random sampling technique. This study used a quantitative method with 148 research respondents from SDIT Wahdah Islamiyah 01 Makassar in grades V and VI. The results of the study showed that there was a significant influence between learning motivation on learning concentration in grade V and VI students of SDIT Wahdah Islamiyah (p = 0.00 <0.05) showing positive results, namely the higher the learning motivation, the more positive the learning concentration. This study is expected to be a guideline for developing the skills of educational institutions and educators in increasing student learning motivation with varied media in the learning process.